Toward a General Conceptualization of Multi-Display Environments - Garcia-Sanjuan, Fernando; Jaen, Javier; Nacher, Vicente (Frontiers in ICT, 2016)
Combining multiple displays in the same environment enables more immersive and rich experiences in which visualization and interaction can be improved. Although much research has been done in the field of Multi-Display Environments (MDEs) and previous studies have provided taxonomies to define them, these have usually consisted of partial descriptions. In this paper we propose a general taxonomy that identifies the key dimensions to tackle when developing MDEs and a classification of previous studies, with the aim of helping designers to identify the key aspects that must be addressed when developing the next generation of MDEs.